2018
DOI: 10.4103/jlp.jlp_78_17
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of lithium estimation for samples collected in different tubes and its stability on storage

Abstract: PURPOSE:Lithium (Li) is a well-established drug for the treatment of bipolar affective disorders. Li as a drug is known to possess a narrow therapeutic index. Thus, regular monitoring of blood Li in patients receiving Li therapy is essential. Plain tubes with clot activator are known to interfere with Li estimation. The current study was planned to compare Li estimation in sera from vacutainers with clot activator, and plasma from sodium heparinized vacutainers with that of Li estimation in sera from glass via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(10 reference statements)
3
0
0
Order By: Relevance
“…13 Ikkurthi et al in their study have concluded that plain vacutainers with clot activators show higher bias and statistically significant higher levels of Li than glass vacutainers. 14 Thus, the study further validates the previous study by Sampson et al 7 in which it was shown that silicone present as an additives in the clot activators vacutainer interacts with the membrane of Li ISE membrane. This interaction results in a false elevation of Li values when estimated on the ISE analyzers.…”
Section: Discussionsupporting
confidence: 89%
“…13 Ikkurthi et al in their study have concluded that plain vacutainers with clot activators show higher bias and statistically significant higher levels of Li than glass vacutainers. 14 Thus, the study further validates the previous study by Sampson et al 7 in which it was shown that silicone present as an additives in the clot activators vacutainer interacts with the membrane of Li ISE membrane. This interaction results in a false elevation of Li values when estimated on the ISE analyzers.…”
Section: Discussionsupporting
confidence: 89%
“…Ikkurthi S et al in their study have concluded that plain vacutainers with clot activators show higher bias and statistically significant higher levels of Li than glass vacutainers[13]. Thus, the study further validates the previous study by Sampson et al .,1997.…”
Section: Discussionsupporting
confidence: 84%
“…[11] In comparison to common laboratories, serum lithium is estimated mainly by ion selective electrode methods which work mainly on the principle of generation potential difference between the electrodes. [12] Ikkurthi S et al in their study have concluded that plain vacutainers with clot activators show higher bias and statistically significant higher levels of Li than glass vacutainers [13]. Thus, the study further validates the previous study by Sampson et al,1997.…”
Section: Discussionsupporting
confidence: 84%